2009
DOI: 10.1002/hec.1511
|View full text |Cite
|
Sign up to set email alerts
|

Regional inequality in China's health care expenditures

Abstract: This paper has two parts. The first part examines the regional health expenditure inequality in China by testing two hypotheses on health expenditure convergence. Cross-section regressions and cluster analysis are used to study the health expenditure convergence and to identify convergence clusters. We find no single nationwide convergence, only convergence by cluster. In the second part of the paper, we investigate the long-run relationship between health expenditure inequality, income inequality, and provinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 14 publications
(16 reference statements)
0
43
0
Order By: Relevance
“…Recently, researchers have realized that public services are important for sustainable development [12][13][14][15], and studies have consequently been carried out measuring regional inequality of public services such as education and health care in China [16][17][18][19]. Nearly all the previous studies used regionally aggregated indicators to measure the regional inequality.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have realized that public services are important for sustainable development [12][13][14][15], and studies have consequently been carried out measuring regional inequality of public services such as education and health care in China [16][17][18][19]. Nearly all the previous studies used regionally aggregated indicators to measure the regional inequality.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the previous studies, this study mainly makes a progress in the following three aspects: (1) The previous studies mainly focus on the regional distribution of a certain kind of healthcare resources as a whole, including the studies on regional distribution of medical institutions [35,36], medical expenses [8], physicians [41][42][43], and medical beds [38][39][40]. However, few studies analyze a certain kind of healthcare resources based on the structural systems themselves deeply.…”
Section: Discussion and Policy Suggestionsmentioning
confidence: 99%
“…Although China has dramatically accelerated economic growth, its regional unbalanced development is also prominent, in particular, there is a considerable disparity between eastern coastal areas and western inland areas in terms of income and public services [7,8]. Most public service resources are strongly concentrated in well-developed regions, especially big cities, while fewer resources are allocated in the western inland and underdeveloped regions [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that government budget deficits have a significant impact, with every 10 million yuan increase in budget deficits associated with an approximate 26.3% decrease in health expenditure in the long term. Based on the same dataset, Chou and Wang (2009) later carried out cross-section regressions and a cluster analysis to prove that provincial government budget deficits are useful in explaining the disparity in health expenditures. Their findings indicate that budget deficits decrease the total health expenditure, which may also extend to GHE.…”
Section: Literature Reviewmentioning
confidence: 99%